(untitled) - Gomez, Kwanchai A (New York, 1984)
Designed for the nonexpert in statistics, this text presents a clear discussion of statistical methods for agricultural research and how to use them. Describes procedures for selecting appropriate experimental design, randomization and layout of experimental plots, data collection analysis, and presentation of results. Uses actual experiments as examples.
Tiểu luận tốt nghiệp - KHCT,Thống kê phép thí nghiệm nâng cao,Thâm cứu phép thí nghiệm sinh học,Thống kê sinh học ứng dụng,Thống kê, phép thí nghiệm ứng dụng,Bố trí thí nghiệm và thống kê,Phương pháp nghiên cứu khoa học công nghệ sinh học,Luận văn tốt nghiệp - KHCT,Thống kê phép thí nghiệm ứng dụng trong DT&CGCT,Xác suất thống kê và phép thí nghiệm - KHCT
Keywords: Agriculture,Field experiments; Research,Statistical methods,Statistical methods